A comprehensive review on bonding between monolithic ceramics and tooth structure with different adhesive agents. - Dingari, Mamatha; Sujesh, M; Ravikumar, C; Rajanikanth, A; Duggineni, Chalapathi Rao; Harilal, G (International Journal of Dental Materials, 2022)
Reliable bonding between the prepared tooth and monolithic ceramics can be achieved by various luting agents available on the market. The selection of luting agent and cementation technique plays an important role in the success of the restoration. With the advent of resin-based adhesive systems as luting agents, clinicians' perspectives have changed to a more conservative approach. Recent systems, chemically adhere the crowns to the prepared tooth structure showing higher bond strength. To reach the aesthetic demands of the patients, all-ceramic restorations were considered over metal-ceramic crowns. Few all-ceramic crowns are brittle, the strength is dependent on the chemical structure and method of fabrication. While some all-ceramic restorations gain strength after cementation. Thus, the choice of luting agent used in cementing all-ceramic crowns is crucial. Even though many luting agents are being introduced no single luting agent fulfilled all the requirements. Among them, adhesive cements showed greater bond strength and enhanced the retention of minimal preparation, which are less retentive. Traditional non-adhesive agents can be used in retentive preparations that bond through mechanical means rather than the chemical bond seen in newer adhesive cements. Also, surface treatments of zirconia showed greater bond strengths irrespective of the luting agent being used. These include air abrasion, acid etching, applying silane couplers, and primers that increase the surface area for adhesion. The use of all-ceramic restorations, the need for surface treatments, types of surface treatments, adhesion and adhesive agents, and evidence from current in vitro research on monolithic ceramics and tooth adhesion were all discussed in this review.